Congestive Adenopathy: A Mediastinal Sequela of Volume Overload. Issue 4 (October 2016) - Shweihat, Yousef R.; Perry, James; Etman, Yasser; Gabi, Ala; Hattab, Yousef; Al-Ourani, Mohammad; Santhanam, Prasanna; Bartter, Thaddeus
Abstract : Background: Endosonography has improved our ability to reach thoracic lymph nodes and to diagnose pathologic conditions with nodal involvement and has lowered the threshold for biopsy. The purpose of this study was to avoid unnecessary procedures, it is important to recognize benign adenopathy. Congestive heart failure (CHF) is both common and a common cause of adenopathy. The purpose of this study was to study the association between CHF and adenopathy and to describe the typical presentation of congestive adenopathy. Methods: We performed a retrospective correlation of computed tomographic (CT) and laboratory findings for patients admitted to hospital with a diagnosis of CHF. Results: Of 500 patients admitted with a diagnosis of CHF, 215 appeared to have CT scans of the chest, and not to have a potentially confounding etiology of adenopathy. The incidence of adenopathy in this study group was 68%. Pulmonary edema on CT and pleural effusion were both significantly associated with adenopathy ( P <0.01 for both). The pattern of congestive adenopathy was one of enlargement of several mediastinal nodes and less likely to involve hilar nodes and single stations in isolation. Conclusion: Congestive adenopathy is common in patients with evidence for acute volume overload. The pattern of presentation should allow clinicians to recognize congestive adenopathy and to separate it from other adenopathy for which biopsy might be appropriate.